Nursing Interventions on the Quality of Life of Cervical Cancer Patients: A Narrative Review - Syifa, Salsa; Adzillah, Finka Laili Nur; Candrawati, Asri Wahyu; Ramadhani, Vania Dwi; Maryati, Ida (International Journal of Nursing and Midwifery Research, 2024)
Cervical cancer is the third most common cancer in women worldwide with 85% of cases occurring in developing countries. Cervical cancer can affect various aspects of the life of sufferers where this is related to the quality of life of cervical cancer sufferers. Therefore, cervical cancer sufferers not only need treatment to improve their physical function, but it is also important to pay attention to aspects of quality of life. The purpose of this study is to find out various interventions that are useful in improving the quality of life in cervical cancer patients. Article searches used the PubMed, CINAHL, and Garuda Kemendikbud databases. The search inclusion criteria were articles discussing breathing exercises for anxiety, full text articles, published in the last 10 years (2012-2022), types of articles in the form of RCT (Randomized Controlled Trial) and Quasi Experiment, in English and Indonesian. From the search results, 1,429 articles were found through the PubMed database, 330 articles through CINAHL, and 31 articles through Garuda Kemendikbud. Then the articles were selected based on inclusion criteria to 1,665 articles. Then the articles were selected based on suitability with the abstract which resulted in 5 articles to be reviewed in this study. Based on the results of the literature review, it was found that interventions could improve the quality of life for cervical cancer patients, namely physical exercise, counselling, electro acupuncture, and comprehensive postoperative care. These results are expected to be a reference and can be directly practiced as an intervention to improve the quality of life of cancer patients